Soft Skills Development in Future Primary School Teacher’s Training - Nataliia Hrona; Olena Vyshnyk; Iryna Pinchuk (Educational Challenges)
The article deals with the importance of having soft skills nowadays. Through the analysis and synthesis of scientific and methodical sources, it was found that soft skills are flexible, sometimes non-special, acme competencies for the successful performance of professional duties.